A Study of the Relationship Between Personal Values and Moral Reasoning of Undergraduate Business Students - Lan, George (Journal of business ethics, 2008)
This study examines values and value types as well as scores in levels of moral reasoning for␣students enrolled in a business program. These two factors are measured using the Schwartz Personal Values␣Questionnaire and the Defining Issues Test 2. No statistically significant differences in levels of moral␣reasoning, rankings of values, and value types could be attributed to gender. However, eight significant correlations between value types and levels of moral reasoning provide evidence that a systematic relationship exists. The relationships are not only internally consistent but also consistent with the model of values based on motivational goals (Schwartz S. H. and K. Boenke: 2004, Journal of Research in Personality, 38 230–255).